Proceedings of the International Conference on Transformations and Innovations in Management 2017
DOI: 10.2991/ictim-17.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Justice Enhances Commitment When Coupled With Empowerment

Abstract: This study explores the impact of organizational justice on employee commitment. It also analyzes the mediating role that psychological empowerment plays in the relationship between organizational justice and empowerment. The sample for this study consisted of 206 respondents from various service sector organizations of Pakistan. The results from the structural equation model analysis revealed that organizational justice was positively related to psychological empowerment and affective commitment. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…OJ has a significant influence on PE and LMX consistent with the existing literature (Durrani et al , 2017; Ionescu and Iliescu, 2021; Kieu, 2023; Kim and Beehr, 2020; Shan et al , 2015; Singh and Singh, 2019). This suggests that promoting fairness and justice in leaders’ practices and procedures, organizations can enhance employees’ attitudes and behavior, ultimately leading to a more engaged and productive workforce.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…OJ has a significant influence on PE and LMX consistent with the existing literature (Durrani et al , 2017; Ionescu and Iliescu, 2021; Kieu, 2023; Kim and Beehr, 2020; Shan et al , 2015; Singh and Singh, 2019). This suggests that promoting fairness and justice in leaders’ practices and procedures, organizations can enhance employees’ attitudes and behavior, ultimately leading to a more engaged and productive workforce.…”
Section: Discussionsupporting
confidence: 90%
“…Employees demonstrate OCB when they perceive fair treatment from their organizations (Elamin and Tlaiss, 2015), especially when they are psychologically empowered (Singh and Singh, 2019). OJ was found to have a significantly positive impact on PE (Durrani et al, 2017;Kim and Beehr, 2020;Singh and Singh, 2019) and PE was found to promote OCB (Newman et al, 2017;Sridadi et al, 2023;Turnipseed and VandeWaa, 2020). It was also suggested and proven that PE has a mediating effect between OJ and OCB (Singh and Singh, 2019).…”
Section: Psychological Empowerment As Mediatormentioning
confidence: 97%
See 2 more Smart Citations